The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1556/650.2015.30240
|View full text |Cite
|
Sign up to set email alerts
|

A veleszületett maxillofacialis deformitások klinikai aspektusai

Abstract: Az ajak-és szájpadhasadék a veleszületett rendellenességek egyik leggyakoribb típusa. A szerzők célja, hogy összefog-laló irodalmi ismereteket nyújtsanak a kórképről. A nemzetközi szakirodalom áttekintésén és megvitatásán túl kiemelik a megelőzés lehetőségeit, a genetikai és környezeti tényezők szerepét, az anatómiai és embriológiai jellemzőket, a prae-és a postnatalis diagnózis és kezelés lehetőségeit. Az etiológia multifaktoriális, mind genetikai, mind környeze-ti faktorok együttes hatása sokszínű fenotípuso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Oral and maxillofacial deformities (OMDF) are characterized as irregularities or malformations in the bones and/or soft tissues of the mouth, jaws, and face. [1–4] Several factors can cause such disease, including cleft lip, cleft palate, cancer, trauma, and automobile accident. [511] It has been reported that about 20% of the world's population have some major OMDF.…”
Section: Introductionmentioning
confidence: 99%
“…Oral and maxillofacial deformities (OMDF) are characterized as irregularities or malformations in the bones and/or soft tissues of the mouth, jaws, and face. [1–4] Several factors can cause such disease, including cleft lip, cleft palate, cancer, trauma, and automobile accident. [511] It has been reported that about 20% of the world's population have some major OMDF.…”
Section: Introductionmentioning
confidence: 99%